Enhancing Employee Potential: Using Talent Mapping to Drive Talent Mobility at PT Mifa Bersaudara - Hadi Firmansah; Fajmal Hadi (Journal Research of Social Science, Economics, and Management, 2025)
In coal mining industries where operational complexity and strategic growth are increasing, the challenge of identifying and developing internal talent is critical. PT Mifa Bersaudara, a coal mining company in Aceh, Indonesia, faces the need to optimize human resource potential to ensure leadership continuity and internal talent mobility. This study aims to implement a systematic talent mapping framework by combining the HAV Matrix and 9-Box Grid to assess employee performance and potential. Employing a quantitative descriptive approach with secondary data from 140 employees, the research uses KPIs, compliance indicators, leadership traits, certifications, and external assessments to evaluate talent readiness. Employees were categorized using a weighted scoring method and visualized in the 9-box grid to support strategic HR decisions. The results revealed that 68 employees fall into the “Developing Top Performers” category and 33 into the “Effective Performers” group, indicating a strong pipeline for future leadership roles. The study concludes that structured talent mapping enhances workforce alignment, boosts employee engagement, and supports sustainable succession planning. It also serves as a reference for other organizations aiming to institutionalize data-driven human resource development.